Active vs. passive recovery during an aerobic interval training session in well-trained runners - Sánchez-Otero, T.; Tuimil, J. L.; Boullosa, D.; Varela-Sanz, A.; Iglesias-Soler, E. (European Journal of Applied Physiology, 2022)
Purpose To compare cardio-metabolic, perceptual and neuromuscular responses to an aerobic interval training (AIT) running session, with active (AR) vs. passive recovery (PR).